Rapid Response to Underweight: Effectiveness of a Short-Term Community-Based Intensive Nutritional Intervention - Muharani, Filly; Febriany, Sekar Elok; Rahmawati, Santi Deliani; Yamin, Imam Syahputra; Mahwati, Yeni; Wisastra, Danan Panggih (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2026)
Background: Childhood stunting and undernutrition remain critical global health challenges. While long-term interventions are common, the efficacy of short-term, community-based intensive nutritional interventions (Pos Gizi) requires further empirical evaluation.Objective: This study aimed to analyze the clinical effectiveness of a 12-day intensive nutritional package on weight and height gain among underweight children under five in Garut District, West Java, using a quasi-experimental one-group pretest-posttest design.Methods: The study included 69 children (aged 10–55 months) meeting the inclusion criteria, who received supplementary feeding and intensive health education over 12 days. Anthropometric data were collected at baseline and endline using standardized instruments. Data were analyzed using the Paired t-test and Cohen’s d effect size calculation.Results: Significant improvements were observed in both weight (p < 0.001) and height (p < 0.001) post-intervention. The mean weight gain was 0.20 kg (95% CI: 0.16–0.25), and the mean height gain was 0.65 cm (95% CI: 0.42–0.88). Effect size analysis indicated a large clinical impact on weight (d = 1.01) and a medium-to-large impact on height (d = 0.68).Conclusion: Short-term intensive nutritional interventions are effective in stimulating rapid weight rehabilitation. While linear growth showed statistical improvement, this likely reflects acute physical recovery rather than permanent structural growth. This model is recommended as an initial acceleration strategy to manage undernutrition.